RANCANG BANGUN SISTEM INFORMASI BERBASIS DEKSTOP PADA KOPERASI MELATI - Kemal Farouq Mauladi (Jurnal Teknika, 2018)
Applications,  Plans  to  Build  Desktop-Based  Information  Systems  on  Melati  Cooperatives,  as  one  form  of organization  are  the  implementing  units  of  members  of  the  welfare  sector  in  this  case  especially  small  and medium entrepreneurs. In making the system, it is necessary to have a system design, the system design used is object-oriented design by making object diagrams, functional models, and ERDs and normalization techniques for data modeling